Effect of isoproterenol on myocardial perfusion, function, energy metabolism and nitric oxide pathway in the rat heart – a longitudinal MR study. (20th February 2014) - Desrois, Martine; Kober, Frank; Lan, Carole; Dalmasso, Christiane; Cole, Mark; Clarke, Kieran; Cozzone, Patrick J.; Bernard, Monique
<x xml:space="preserve">Abstract</x> The chronic administration of the β‐adrenoreceptor agonist isoproterenol (IsoP) is used in animals to study the mechanisms of cardiac hypertrophy and failure associated with a sustained increase in circulating catecholamines. Time‐dependent changes in myocardial blood flow (MBF), morphological and functional parameters were assessed in rats in vivo using multimodal cardiac MRI. Energy metabolism, oxidative stress and the nitric oxide (NO) pathway were evaluated in isolated perfused rat hearts following 7 days of treatment. Male Wistar rats were infused for 7 days with IsoP or vehicle using osmotic pumps. Cine‐MRI and arterial spin labeling were used to determine left ventricular morphology, function and MBF at days 1, 2 and 7 after pump implantation. Isolated hearts were then perfused, and high‐energy phosphate compounds and intracellular pH were followed using 31P MRS with simultaneous measurement of contractile function. Total creatine and malondialdehyde (MDA) contents were measured by high‐performance liquid chromatography. The NO pathway was evaluated by NO synthase isoform expression and total nitrate concentration (NOx). In IsoP‐treated rats, left ventricular mass was increased at day 1 and maintained. Wall thickness was increased with a peak at day 2 and a tendency to return to baseline values at day 7. MBF was markedly increased at day 1 and returned to normal values between days 1 and 2. The rate–pressure product and phosphocreatine/adenosine triphosphate ratio in perfused hearts were reduced. MDA, endothelial NO synthase expression and NOx were increased. Sustained high cardiac function and normal MBF after 24 h of IsoP infusion indicate imbalance between functional demand and blood flow, leading to morphological changes. After 1 week, cardiac hypertrophy and decreased function were associated with impaired phosphocreatine, increased oxidative stress and up‐regulation of the NO pathway. These results provide supplemental information on the evolution of the different contributing factors leading to morphological and functional changes in this model of cardiac hypertrophy and failure. Copyright © 2014 John Wiley & Sons, Ltd.